Green Synthesis and Antimicrobial Studies of Ni(II) and Zn(II) Dinuclear Schiff Base Complexes - Kassim, Karimah; Azwan Hamali, Muhamad (International Journal of Engineering and Technology, 2018)
A series of tetradentate Zn(II) and Ni(II) Schiff base complexes derived from N,N-Bis-(2-hydroxyl-5-methoxybenzaldehyde)-m-phenylenediamine was synthesized using microwave assisted synthesis approach for 5-15 minutes. The confirmation of the ligand as well the respective complexes has been elucidated through physiochemical and spectroscopy analyses. The studies show that two metal ions formed bridges connecting two Schiff base ligands. The nitrogen and oxygen atoms in each ligand served as coordination sites for the metal ions. The Schiff base ligand and complexes were screened for antimicrobial properties using Disc diffusion method against Escherichia coli, Bacillus subtilis, Enterobacter cloacae, and Klebsiella pneumoniae. The screening shows that both Zn(II) and Ni(II) complexes give signif-icant inhibition towards the bacteria tested.Â Â